The Effect of Pyriproxyfen on Eggs and Female Adults Production of The Sitophilus oryzae L. - Shefik, Maan (Iraqi Journal of Science, 2023)
A series of tests were conducted to determine the susceptibility of eggs and neonates of the Rice Weevil Sitophilus oryzae L. (Coleoptera: Curculionidae), exposed to the insect growth regulator, Pyriproxyfen, on filter paper and on rough rice. In the first test, the hatch rate of eggs exposed on filter paper treated with Pyriproxyfen at the label rate of 0.003 mg [AI] /cm2 when used as a surface treatment in structures was 52.0 ± 7.3% compared to 93.0 ± 3.3% on untreated controls. In the second test, eggs were exposed to a dose-response series of 0.00003 to 0.03 mg [AI]/ cm2. Egg hatch was directly proportional to concentration and anged from 85.0 ± 2.0% on untreated controls to 26.7 ± 8.3% at the highest concentration tested. In the third test, 1 ppm of Pyriproxyfen was sprayed on long grain rough rice (paddy), and then individual kernels were cracked and an egg of S. oryzae was placed directly on the kernel. On untreated rice kernels, 67.5 ± 11.6% of the eggs hatched and were able to bore inside and all of these larvae emerged as adults. In contrast, 40.0 ± 5.3% of the eggs placed on treated cracked kernels were able to develop, but none emerged as adults. In the final test, newly emerged adults were exposed on rough rice treated with 1 ppm Pyriproxyfen. The number of eggs from adults on untreated rice was 52.1 ± 4.3 eggs per female, and on treated rice the average egg production was 12.5 ± 1.1 eggs per female. Pyriproxyfen applied on a surface or on rough rice affected development of egg hatch also reduced fecundity of parent adults exposed on the treated rough rice.